Hygrothermal degradation of elastic properties of fiber reinforced composites: A micro-scale finite element analysis - Gholami, Meghdad; Afrasiab, Hamed; Baghestani, Ali Mohammad; Fathi, Alireza (Composite structures, 2021)
In this paper, the effect of hygrothermal conditions on elastic properties of polymeric composite materials is investigated by the finite element method. A micromechanical degradation model is developed based on Fick’s second law utilizing an ABAQUS python scripting micro modeling (APSMM) and an ABAQUS parallel finite element analysis (APFEA). The APSMM algorithm is used to study the degradation of elastic constants of a fiber-reinforced polymeric composite (AS/3501–5) under specific hygrothermal conditions, while, the APFEA scheme is employed to solve the problem under time-dependent (transient) hygrothermal conditions. The results are verified against available experimental data. The main advantage of the proposed methods is that by experimentally determining the composite material properties only at one particular temperature and humidity condition, these properties can be obtained after any time of exposure to constant or time-varying hygrothermal conditions. Furthermore, these methods can be extended to analyze different types of composites with any kind of material and/or construction.